Cardiologic safety of menopausal hormone therapies - Stachowiak, Grzegorz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2009)
Cardiovascular diseases appear to be the most frequent concomitant illnesses of the menopausal period. They are not only the main reasons of women’s deaths in the Western countries but also the most serious (but fortunately rare) complications of menopausal hormone therapies (MHT). In this article some cardiovascular risk factors influencing circulatory complications of MHT together with authors’ point of view concerning therapeutic safety were discussed. A particular attention has been paid to the choice of proper progestogen what plays a crucial role in the area of MHT safety.